Society, morality, embodiment: Tracing Durkheim's legacy - Hausner, S (Berghahn Journals, 2017)
This issue of Durkheimian Studies presents the collective efforts of the participants of a workshop held in late 2017, the centenary anniversary of Émile Durkheim’s death, at the University of Oxford. The articles that emerged from it, published together in this special issue for the first time along with some new material, demonstrate a continuation of classic Durkheimian themes, but with contemporary approaches. First, they consider the role of action in the production of society. Second, they rely on authors’ own ethnographies: the contributors here engage with Durkheimian questions from the data of their own fieldsites. Third, effervescence, one of Durkheim’s most innovative contributions to sociology, is considered in depth, and in context: how do societies sustain themselves over time? Finally, what intellectual histories did Durkheim himself draw upon – and how can we better understand his conceptual contributions in light of these influences?